Cellulose Nanocrystals: A Versatile Nanoplatform - Dhurjad, Lekha; Sagle, Dhanshri; Deshmukh, Amol; Narkhede, Minal (Asian Journal of Pharmaceutical Research and Development, 2020)
The developing natural and ecological awareness has driven endeavors for advancement of new inventive products for different end-use applications. Nanotechnology executes a significant contribution in the improvement of such product. Cellulose nanocrystals are one of a kind nanomaterial obtained from the most copius and practically boundless natural polymer, cellulose. These nanomaterials have obtained remarkable interest due to their mechanical, optical, chemical, and rheological properties. Cellulose nanocrystals basically derived from naturally existing cellulose fibres, are biodegradable and inexhaustible in nature and consequently they fill in as an eco-friendly material for most applications. Considering the ever-expanding interdisciplinary research being done on cellulose nanocrystals, this review means to collate the information accessible about the preparation technique, modification and application of cellulose nanocrystals. Cellulose nanocrystals can be sourced from biomass, plants, or microbes, depending on genuinely basic, versatile, and productive isolation methodology. Mechanical, synthetic, and enzymatic treatments, or a blend of these, can be utilized to separate nanocellulose from natural sources. Nanocrystalline cellulose surface modification strategies are commonly used to introduce either charged or hydrophobic moieties, and comprises amidation, esterification, etherification, silylation, polymerization, urethanization, sulfonation, and phosphorylation. This nanomaterial is a promising contender for applications in fields, for example, biomedical, pharmaceuticals, electronics, barrier films and so forth.